Analysis of Factors Affecting Muslim Millennial Investors in Using Online Trading Systems in Medan City - Dewi, Sartika (Jurnal Riset Akuntansi dan Keuangan, 2024)
The purpose of this study is to increase public knowledge, especially in the millennial generation, so that awareness of interest in investing will increase because it has an impact on the country's and personal economies. Researchers conducting research are using quantitative methods. This type of research data is primary data collected by distributing questionnaires online via Google From. Researchers used Structural equation modelling-partial least square data analysis assisted by SmartPLS4 software. Based on the results of the research that has been done, it can be concluded that personal interests, investment risk, and online trading system facilities have a positive effect on Muslim millennial investors use of the online trading system. The implication of this research is that personal interests are a strong and significant influence on millennial investors' decisions to use online trading systems.